Hubungan Hubungan Mutu Asuhan Gizi Dengan Lama Rawat Inap Pasien Di Rumah Sakit : Literature Review: Hubungan Mutu Asuhan Gizi dengan Lama Rawat Inap Pasien di Rumah Sakit: Sebuah Studi Literatur - Yenni, Fitri; Purba, Martalena BR.; Syauqy, Ahmad (Amerta Nutrition, 2024)
Background: Inpatients' needs for nutrition are fulfilled by providing food services based on their specific requirements. Further, interventions focusing on improving their nutritional wellbeing can reduce their length of stay and at the same time improve the hospital's service quality. Objectives: The objective of this study is that to identify the relationship between quality of nutritional care and the patient's length of stay. Methods: This research reviews past quantitative studies available in the databases of NCBI-PUBMED, Springer Link, Cochrane and Google Scholar. They must be peer-reviewed articles published in English from 2017 to 1 October 2022, and the mean age of the patients being discussed is 18 years or more. As this study only reviews full articles, abstract-only texts were excluded. In addition, the data form the selected papers were extracted by three researchers. Discussion: From many factors influencing patient's length of stay, besides the fact that comorbidities affect the duration of the disease suffered by the patient, malnutrition during illness is the most dominant one. Comorbidities affect the duration of the disease suffered by the patient. Length of stay is influenced by patients' nutritional intake, so screening on which at hospital admission is crucial for their health status and length of stay. Conclusions: For hospitals, improving the quality of their nutrition services helps focus their attention to nutritional care, and rapid intervention can shorten length of stay. In addition, malnutrition is significantly worsened by mealtime barriers and poor food intake and prolongs length of stay.